Impact of fertilization with pig slurry on the isotopic composition of nitrate retained in soil and leached to groundwater in agricultural areas. (February 2021) - Margalef-Marti, Rosanna; Llovet, Alba; Carrey, Raúl; Ribas, Angela; Domene, Xavier; Mattana, Stefania; Chin-Pampillo, Juan; Mondini, Claudio; Alcañiz, Josep M; Soler, Albert; Otero, Neus
Abstract: The isotopic composition of N and O of nitrate (NO3 − ) is usually employed to trace its sources of pollution in groundwater. In agricultural areas, the amount of NO3 − that reaches the aquifers after fertilization is controlled by different transformation processes that can affect the nitrogen species isotopic composition. Aiming to address the reliability of using isotope tools to trace sources of groundwater NO3 −, the goal of this study was to check the effect of fertilization on the isotopic composition of N compounds retained and leached from soils. The concentration and isotopic composition ( δ 15 N and δ 18 O) of ammonium (NH4 + ), NO3 − and nitrite (NO2 − ) was characterized after the application of pig slurry in lysimeters containing either soil under fallow (LF) or the same soil continuously cropped and fertilized (LC) during the previous six years. Results showed that the leached NO3 − isotopic signature did not directly reflect the isotopic composition of the applied pig slurry. Just after fertilization, nitrification led to lower δ 15 NNO3 values in soil extracts and leachates (e.g. from +5.9 ± 0.9‰ to +3.8 ± 3.1‰ in soil extracts of LF lysimeters). These values increased after complete nitrification (+11.5 ± 1.3‰) towards the δ 15 Nbulk of pig slurry (+19.6 ± 0.5‰). Later on, due to soil organic matter and plant debris mineralization and subsequent nitrification, values decreased towards the initial δ 15 NNO3 of soil but remained above them (+8.6 ± 1.0‰). Both LF and LC experiments showed a similar trend and the latter ones allowed to reinforce that long-term fertilization with pig slurry can increase the soil δ 15 NNO3 . Concerning the δ 18 O of NO3 − from soil extracts and leachates, it mainly depended on the δ 18 O of irrigation water and oxygen, after nitrification of NH4 + from pig slurry. Therefore, studies aiming to trace groundwater NO3 − pollution sources in rural areas by using an isotopic approach should consider the fertilization history of each setting. Also, analyzing the δ 15 Nbulk of soil is recommended, since it could mask the isotopic signature of the N applied through fertilization. Graphical abstract: Image 1 Highlights: Pig slurry application increased the δ 15 N of soil NO3 − after 8 months. SOM and plant debris mineralization masked the pig slurry δ 15 N on leached NO3 − δ 18 O of leached NO3 − depended on the δ 18 O of H2 O and O2 . Fertilization history must be considered to trace NO3 − sources with isotope data.